ANALISIS EPIDEMIOLOGI PENYAKIT TUBERCULOSIS PARU DI PUSKESMAS KOYA TAHUN 2021-2023 - Lele, Gabriella Charoline; Telew, Agusteivie; Supit, Alva (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Tuberculosis is a disease caused by Mycobacterium tuberculosis which most often attacks the lungs. The source of infection, TBBTA patients were positive through splashes of phlegm they expelled. Epidemiologically, tuberculosis more often attacks the productive age group, but in all age groups there are many people affected by tuberculosis. The aim of this research is to analyze the epidemiology of tuberculosis, as well as analyze the factors of age, gender and occupation of tuberculosis sufferers at the Koya Health Center, South Tondano District. Using quantitative descriptive methods and the analysis used is univariate analysis. Respondents totaled 107 tuberculosis patients. Based on the results of data analysis, it is known that based on the patient's age category, namely 15>50 years, the number is 58.9% with a frequency of 63, and at ages>50 years it is 41.1% with a frequency of 44. Furthermore, for the first gender category, male there were 63 people with a percentage of 59.9%, and 44 women with a percentage of 41.1%. Next, in the non-employed worker category there were 15 people with a percentage of 14%, then there were 45 people in the private sector with a percentage of 42.1%, and finally there were 47 civil servants with a percentage of 43.9%. This statement provides an initial description of the prevalence of pulmonary TB in the population studied. In conclusion, the majority of sample respondents are under 50 years old, while only a small portion are over 50 years old. The majority of survey respondents were men with a proportion of around 58.9% of the total surveyed population. Meanwhile, the number of women who took part in this survey was smaller, namely around 41.1% of the total respondents. The majority of the 107 individuals surveyed were workers, which is around 85.9% of the total sample. Of those who work, the majority are divided between private sector (42.1%) and civil servants (43.9%). Despite this, about 14% of the total sample is unemployed. This information provides an overview of the prevalence of pulmonary TB in the studied population, which can be used to analyze risk factors and the effectiveness of preventive and treatment measures.